Fluoxetine enhances maximal electroshock seizure threshold in Albino rat model when compared to phenytoin - Gangopadhyay, Tanmoy; Mandal, Ananya; Keshri, Uma Shanker (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Individuals with epilepsy have a higher incidence of psychiatric disorders than person without epilepsy. Epidemiological studies have shown that the co-morbidity of epilepsy and depression to be high as 50%. The conventional anti-depressants are believed to lower the seizure threshold making it difficult to treat the co-morbid depression, but animal studies have shown SSRIs, a common anti-depressant, to have anti-convulsant properties. So, we propose to study the anticonvulsant effects of fluoxetine, a SSRI, in albino rats against maximal electroshock seizure and to compare against a standard antiepileptic drug phenytoin. Methods: The anticonvulsant effect of fluoxetine was observed in model of maximal electroconvulsive seizure threshold in albino rats. The animals were divided into 3 groups having 6 animals each, receiving distilled water, fluoxetine and phenytoin respectively. The drugs were given orally, and the effect was observed on day 7, 14 and 21. Tonic hind-limb extension was taken as the parameter of electroshock seizure. The effects were compared against a standard anti-seizure drug phenytoin. Results: Fluoxetine showed significant elevation of the seizure threshold following 14 days of administration (P value 0.031). The effect was comparable to phenytoin with no significant difference after 7, 14 and 21 days of treatment (P-value 0.485, 0.699 and 0.818 respectively) though phenytoin showed significant anti-seizure effect since day 7 of treatment. Conclusions: Fluoxetine showed significant anti-seizure activity against electroconvulsive seizure in albino rats.